2009
DOI: 10.1111/j.1525-1446.2009.00809.x
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Care Utilization in a Conflict‐Affected District of Northern Sri Lanka

Abstract: Provision of field antenatal clinics, early entry to ANC, and domiciliary care by PHM need improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…This study also highlighted that women in conflict areas faced a higher risk of sexual and physical abuse, and faced various barriers in receiving adequate health care and services [ 20 ]. Furthermore, antenatal care utilization was shown to be significantly poor for women whose families were affected by conflict in Northern Sri Lanka or living in an active conflict zone in a study conducted in 2009 [ 21 ].…”
Section: Physical Health Impactmentioning
confidence: 99%
“…This study also highlighted that women in conflict areas faced a higher risk of sexual and physical abuse, and faced various barriers in receiving adequate health care and services [ 20 ]. Furthermore, antenatal care utilization was shown to be significantly poor for women whose families were affected by conflict in Northern Sri Lanka or living in an active conflict zone in a study conducted in 2009 [ 21 ].…”
Section: Physical Health Impactmentioning
confidence: 99%
“…Unlike recent trends in Egypt, the odds of maternal care increased during conflict as maternal age increased. Research from Nepal, Sri Lanka and Yemen indicated a negative association of conflict with age, while Iraq reported lower use of SBA (22%) among women under 25 [ 14 , 43 – 49 ]. Also contrary to recent trends in Egypt, and evidence elsewhere, odds of maternal care use during conflict did not increase with increased educational attainment [ 2 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from conflict-affected countries shows that conflicts adversely affect population health and maternal care by restricting timely availability and access to quality care [ 12 – 14 ]. Addressing equity in maternal care is challenging in conflict-affected settings, particularly during acute conflict [ 4 , 15 – 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pregnant women in South Sudan often experience considerable time delays when trying to reach a health facility for treatment (Karoshi & Keith, 2009;Sivaganesh & Senarath, 2009). Geographic barriers impede women with obstetric complications from accessing emergency obstetric care (Borghi, Ensor, Somanathan, Lissner, & Mills, 2006).…”
Section: Geographicalmentioning
confidence: 99%